Translation, Cultural Adaptation and Validation of the Current Opioid Misuse Measure for European Portuguese - Mendes-Morais, Diogo (2020)
Introduction: Current practice guidelines recommend using Current Opioid Misuse Measure to screen aberrant opioid-related behaviors in chronic pain patients. Our aims were to translate, adapt and validate it to be used in Portuguese chronic pain patients.Material and Methods: Translation and cultural adaptation process followed guidelines and a model of principles for good practice. Adult chronic pain patients on opioid therapy, from one major hospital in Portugal, were invited to complete the translated version. Descriptive statistics, Cronbach’s alpha, inter-item, item-total and intra-class correlation coefficients and principal components analysis were applied.Results: Translation process was performed as planned and the validation sample was composed by 98 patients (median age = 62.5 years). Regarding internal consistency, a global Cronbach’s alpha of 0.778 was obtained and item-total correlations of all items were above 0.20 with four exceptions. An intra-class correlation coefficient of 0.90 was found between test and retest. Regarding validity, all 17 items presented a content validity index above 0.80. Six principal components were extracted and explained 66.3% of the variance.Discussion: The Portuguese version of Current Opioid Misuse Measure was properly translated, adapted and validated; showing good quality in terms of reliability and validity. This is the first instrument to screen aberrant opioid-related behaviors in Portuguese chronic pain patients. Consequently, it will aid and promote the identification of opioid misuse in these patients.Conclusion: The implementation of this questionnaire may reduce the incidence and morbimortality of opioid misuse among chronic pain patients and should improve chronic pain treatment in Portugal.